Evaluation of brewery by-products replacing vitamin premix in broiler finisher diets - Gondwe, T N P; Mtimuni, J P; Safalaoh, A C L (The Indian Journal of Animal Sciences, 2012)
The effect of sun-dried spent yeasts (SY), spent grains (SG) and local brewer's grains (LB) in broiler finisher diets was studied in an 8-week feeding trial involving 2 strains of broilers, Cobb 500 and Indian river chickens. Chicks (400) were fed standard broiler starter ration from day-old to 4 weeks and thereafter split into groups of 20 chicks / strain a treatment of maize/soybean-based ration supplemented with SY, SG, and LB at 5 % level. A ration supplemented with vitamin premix (VT) was taken as a standard while a ration without any supplement (ZR) was a control. Live weights and weight gains were not affected by substitution of vitamin premix with SY, SG or LB. The birds on ZR performed equally better as the birds on the standard (VT) ration. The birds on SY were superior to the birds on other ration supplements including the standard (VT) ration in live weights and weight gains, the effects were significant (P